The effect of red cabbage extract to serum MDA levels in rats after maximum physical activity - Haris, Nadia Husna; Nugroho, Trilaksana; Utomo, Astika Widy; Yora Nindita (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2021)
The maximum physical activity led to generate of free radical levels in the human body called oxidative stress. Red cabbage is well known as the vegetable containing highest anthocyanin among various other head cabbage plants. Anthocyanin is an antioxidant which is proven can prevent oxidative stress through reduction of MDA levels. The study aimed to investigate the effect of red cabbage extract (RCE) on MDA levels in rat after doing maximum physical activity. It was a true experimental study with post-test only control group design. Twenty-four male albino Wistar rats were used in this study. The rats were randomly divided into four groups i.e. the rats receiving maximum physical activity without and with RCE administration at dose of 86 mg/kg BW for eight days and the rats not receiving maximum physical activity without and with RCE administration. A swim test was used for maximum physical activity intervention. Serum MDA levels were measured using TBARS method. Data were analysed using one-way Anova followed by post-hoc LSD. A p value <0.005 was considered to be significant. The results showed that the rats treated with RCE both receiving maximum physical activity or not showed significant MDA reduction compared to rats without treated RCE (p=0.011 and p=0.027, respectively). Meanwhile, there was no significant difference in serum MDA levels between rats treated with RCE receiving maximum physical activity and rats not treated with RCE and not receiving maximum physical activity (p=0.540). Supplementation of RCE can reduce serum MDA levels in rats with and without maximum physical activity. Further study to investigate effective dose of RCE is recommended.